The Danube as an Artistic Image in European Modern Literature (Based on the Material of the Book "Danube" by Claudio Magris) - Dzikovska, Larysa (Journal of Danubian Studies and Research, 2023)
Claudio Magris is an Italian writer, journalist, essayist; laureate of many awards, including “Erasmus” (2001) and the Charles Veyonne Award (2009). His book “Danube”, which was written in 1986, won the Bagutta prize and is devoted to Central Europe, the history and culture of countries along the entire river flow of the Danube, the most important artery in Europe, – in the most expressive forms and will be the subject of scientific and journalistic conversation. The idea that the peaceful coexistence of different peoples, the combination and fusion of different elements is the key to a prosperous, happy life, runs through the entire book. At the same time, Magris emphasizes that not only peoples, but also each person is the result of mixing different traditions and cultures. Getting to know the “Danube” is really enriching: the author not only sincerely shares his knowledge, but also teaches to see the events and characters differently, in fact, teaches to think differently. Today this book acquires modern sound and understanding.